A theory grounded framework of information behaviour of SMEs on emerging information communication technology adoption decision-making. (7th April 2022) - Eze, Sunday Chinedu; Olatunji, Sulaimon; Chinedu-Eze, Vera C.; Inegbedion, Henry; Bello, Adenike
Although studies have made significant efforts to study information behaviour using numerous model and extended ones, many have extrapolated the findings of others as if small and medium enterprises (SMEs) operate in the same way other sectors do. This has slowed down the development of an integrated framework aimed at understanding the information behaviour of SMEs. The paper, examines information behaviour of SMEs by explicitly exploring the determinants of perceived information need for EICT adoption by SMEs, information source selection for EICT adoption by SMEs and factors influencing information sources selection for new ICT adoption by SMEs. Qualitative approach was adopted with the use of unstructured and semi-structured interviews with 20 participants drawn purposeful from Luton directories. The study developed an integrated framework underpinned by the TOE framework and helped identify the critical determinants of perceived information need, information sources selection when the need for EICT arises and factors influencing SMEs information source selection for EICT adoption decision-making.